Lithium ion battery component with multiple layers of electrodes

By adopting the current collector design of foam metal and microporous carbon layer or elastomer structure in lithium-ion batteries, the stress fluctuations and strain accumulation problems caused by changes in metal anode volume are solved, the cycle stability and life of the battery are improved, and the battery is reduced. The stacking pressure requirement simplifies the battery packaging process.

CN119252930APending Publication Date: 2025-01-03FORD GLOBAL TECH LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410819055.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-27
Filing Date
2024-06-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The metal anode in lithium-ion batteries undergoes large volume changes during charging and discharging, resulting in stress fluctuations and strain accumulation, affecting battery performance and life, and the stacking pressure demand is high, making it difficult to effectively maintain interface contact within the battery cell.

Method used

A secondary solid-state battery (SSB) electrode structure was designed, using a current collector configuration in which foam metal is enclosed between two microporous carbon layers, or an elastomeric structure sandwiched between two metal foil layers, through carbon fibers Paper and conductive polymer layers to relieve strain and pressure, forming electrode assembly to enhance mechanical stability.

Benefits of technology

Effectively reduce stress fluctuations, alleviate strain accumulation, reduce stacking pressure needs, improve cycle stability and battery life, reduce operating stacking pressure, simplify battery packaging process, and do not increase manufacturing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252930A_ABST
    Figure CN119252930A_ABST
Patent Text Reader

Abstract

The present disclosure provides a lithium ion battery component with multiple layers of electrodes. The present disclosure relates to a secondary solid state battery having a current collector configuration comprising a foam metal sandwiched between two microporous carbon layers. The current collector is directly interfaced with both the negative electrode and the solid electrolyte separator. Alternatively, the current collector may include an elastomer sandwiched between a pair of metal foil layers, thereby achieving responsive expansion and contraction as a function of changes in the electrode during a charge-discharge cycle. Another embodiment envisages a carbon fiber paper current collector located between two microporous layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to electrode materials for lithium-ion batteries. Background Art

[0002] Advances in battery technology can impact advancements in a variety of fields, including electric vehicles and portable electronics. Solid-state batteries (SSBs) have attracted attention due to their potential increased specific energy density and volumetric energy density. To maximize the benefits of SSBs, metal anodes such as lithium (Li) or silicon (Si) are typically used.

[0003] However, these anodes may experience large volume changes during battery charging and discharging. This volume change may require stacking pressures (ranging from 5 MPa to 50 MPa) to maintain interfacial contacts within the battery cell. Moreover, even at these stacking pressures, performance degradation may occur in Li or Si SSBs. This is partly due to stress fluctuations in the electrodes and the resulting strain accumulation. Summary of the invention

[0004] The present disclosure relates to a design for a secondary SSB. The cell consists of a negative electrode, a solid electrolyte separator, and a current collector. The current collector is characterized by a configuration in which a metal foam is enclosed between two microporous carbon layers. One of these carbon layers maintains direct surface contact with the negative electrode, while the other contacts the solid electrolyte separator. This configuration results in a surface of the current collector that is smoother than the surface of the metal foam.

[0005] A microporous carbon layer, which may be composed of nano-sized carbon particles, may be coated on the metal foam. The metal foam may be a copper (Cu) metal foam, and its thickness is intended to be greater than the thickness of each of the microporous carbon layers.

[0006] In addition, the design may include a positive electrode that maintains direct surface contact with a solid electrolyte separator. When these components (positive electrode, current collector, solid electrolyte separator, and negative electrode) are combined, they form an electrode assembly. The battery may feature several such assemblies with carbon fiber paper interleaved between them so that not all adjacent assemblies are in direct contact. Instead, some adjacent assemblies are separated by carbon fiber paper.

[0007] Another contemplated embodiment involves a current collector comprised of an elastomer sandwiched between two metal foil layers. These layers are arranged so that one maintains direct surface contact with the positive electrode while the other contacts the solid electrolyte separator. This structure enables the current collector to compress or expand in response to the expansion or contraction of the positive and negative electrodes during charge and discharge, respectively.

[0008] These metal foil layers can be the same material or different materials, and the elastomer can potentially be silicone rubber. Likewise, these components (positive electrode, current collector, solid electrolyte separator and negative electrode) can form an electrode assembly. These assemblies can be multiplied and interlaced with carbon fiber paper.

[0009] In another embodiment, the current collector may be a carbon fiber paper current collector. In this contemplated embodiment, the current collector comprises a carbon fiber layer sandwiched between two microporous layers, wherein the surface roughness of the carbon fiber layer is compensated by the coating of the microporous layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1A is a schematic cross-section of a current collector comprising carbon fiber paper;

[0011] Figure 1B is a schematic cross section of an anode coating on a current collector;

[0012] Figure 2A is a schematic cross-sectional view of a single battery cell device with a carbon fiber paper current collector;

[0013] Figure 2B is a schematic cross-sectional view of a battery cell stack arrangement with a carbon fiber paper current collector;

[0014] Figure 3 is a schematic cross section of carbon fiber paper as a strain buffer in a secondary SSB battery cell stack;

[0015] Figure 4 is a schematic cross section of an elastic material sandwiched between two metal foils;

[0016] Figure 5 is a schematic diagram of a metal foam coated with a microporous layer; and

[0017] Figure 6 Schematic diagram of the conductive polymer current collector in the secondary SSB battery cell. DETAILED DESCRIPTION

[0018] Embodiments are described herein. However, it should be understood that the disclosed embodiments are merely examples and that other embodiments may take various and alternative forms. The drawings are not necessarily drawn to scale. Some features may be enlarged or minimized to show details of particular components. Therefore, the specific structural details and functional details disclosed herein should not be interpreted as limiting, but merely as a representative basis for teaching those skilled in the art.

[0019] The various features shown and described with reference to any one of the accompanying drawings may be combined with features shown in one or more other drawings to produce embodiments not explicitly shown or described. The combinations of features shown provide representative embodiments for typical applications. However, for specific applications or implementations, various combinations and modifications of features consistent with the teachings of the present disclosure may be desired.

[0020] Measures that can mitigate stress fluctuations, relieve strain accumulation, and reduce the need for stacking pressure are desirable. Such measures can enhance cycle stability and battery life, which represents a significant advance in battery technology. The disclosed embodiments can alleviate the challenges associated with volume changes in SSBs. They introduce an elastic conductive layer that can be used as a current collector or a separate strain buffer. The layer can be used for SSBs that exhibit significant volume changes during charge and discharge, such as those based on metal anodes (such as Li metal and Si).

[0021] The conductivity of the layer should exceed 1 S / cm, ideally more than 10 S / cm. To accommodate SSB anode volume changes, the elasticity of the layer should be able to compensate for strains, for example, 40% strain under a compressive stress of 1.5 MPa. Ideally, the layer should have a compressive elastic modulus ranging between 1 MPa and 10 MPa and a strain range (up to 60%). The thickness of the layer should be small, ideally less than 80 microns in the uncompressed state.

[0022] In one embodiment, carbon fiber paper can be used as a current collector. In another embodiment, a microporous layer composed of nano-sized carbon particles ensures a smooth surface for coating the Si anode layer. In another embodiment, a sandwich configuration of an elastic material between two metal layers is envisioned. In this design, an elastic material (such as silicone rubber) is sandwiched between two metal foils. The metal foil provides electrical connection, and the spring-like intermediate layer shrinks when the electrode expands, thereby releasing the strain of the electrode active material. When the active material shrinks, the layer rebounds to keep the particles in close contact. The properties of the elastic material (such as elastic modulus and thickness) can be customized to meet expansion requirements and contraction requirements. The thickness of the metal foil can be in the range of 2μm to 5μm to minimize the total thickness of the current collector. The metal foil can be the same metal (such as Cu foil or Al foil) or different metals (one side can be Cu foil and the other side is Al foil).

[0023] In another embodiment, a metal foam can be used as the primary elastic component, with a microporous (carbon) layer coated on top of it to tune the surface roughness and enhance electrical contact. The elastic properties of the metal foam can be designed as desired. The microporous layer composed of nano-sized carbon particles is used to ensure a smooth surface for coating the Si anode layer.

[0024] The present disclosure relates to cycling stability, thereby increasing the life of metal anode based SSBs. Another potential benefit of the present disclosure is to reduce the operating stacking pressure, which is currently challenging for battery packaging in electric vehicles. The present disclosure has the potential to reduce the stacking pressure to less than 1 MPa, thereby simplifying battery packaging.

[0025] Furthermore, the envisioned embodiments do not increase battery manufacturing complexity. For example, the new current collector is a direct replacement for current metal foils in a roll-to-roll process. Strain buffer layers can be easily inserted between individual battery cells.

[0026] Figure 1A An illustrated embodiment of a carbon fiber paper is provided. This carbon fiber paper, indicated generally at 10, is a composite structure comprising a core carbon fiber layer 12 encapsulated between two microporous layers, indicated respectively at 14 and 16. The microporous layers 14 and 16 include a plurality of nano-sized carbon particles 18, which are effectively embedded in the microporous layers.

[0027] The presence of these microporous layers 14, 16 on both sides of the carbon fiber layer 12 not only helps to enhance the mechanical stability of the carbon fiber paper 10, but also serves to make its surface smoother. This enhanced surface smoothness is advantageous when the Si anode layer is subsequently applied, thereby facilitating adhesion and uniform coverage of the layer.

[0028] In one embodiment, the carbon fiber paper 10 acts as a current collector within the construction of the SSB. In this function, it is configured so that one of the microporous layers (e.g., 14) is in direct face contact with the negative electrode, while the other microporous layer (e.g., 16) is in direct face contact with the solid electrolyte separator. The result of this arrangement ensures that the surface of the current collector is smoother than the surface of the constituent metal foam.

[0029] Convert to Figure 1B , depicts the process of coating Si anode slurry (indicated by numeral 20) onto carbon fiber paper 10. Once applied, the Si anode slurry 20 assumes the role of the negative electrode.

[0030] It is noteworthy that nano-sized carbon particles 18 are incorporated into the microporous layers 14, 16 for enhancing conductivity and promoting efficient electron transfer within the battery. In certain embodiments, the carbon fiber layer 12 may be in the form of a foamed metal such as Cu. The size of the foamed metal layer may be such that its thickness exceeds the thickness of each of the microporous carbon layers 14, 16.

[0031] After the coating process, a solid electrolyte separator is applied so that it is in direct contact with one of the microporous layers 16 of the carbon fiber paper 10. Furthermore, in some configurations, a positive electrode may be introduced into the battery structure, the positive electrode being arranged so that it is in direct facing contact with the solid electrolyte separator.

[0032] This outlined configuration forms an integrated electrode assembly comprising: a positive electrode, a current collector which may be carbon fiber paper 10, a solid electrolyte separator, and a negative electrode which may be applied as a Si slurry. Multiple such electrode assemblies and carbon fiber papers may be assembled in an interlaced manner. Adjacent pairs of the electrode assemblies may be separated by one of the carbon fiber papers.

[0033] Continue to refer Figure 2A , shows the battery cell structure in the embodiment mentioned. The battery cell includes carbon fiber paper 10 as a base layer. On top of the base layer, a Si anode layer 22 is deposited, which represents the negative electrode in the battery cell structure. The Si anode layer 22 directly interfaces with the microporous layer 14 of the carbon fiber paper 10, thereby benefiting from the smoother surface provided by the microporous layer.

[0034] After the Si anode layer 22, a solid electrolyte separator 24 is applied, which interfaces directly with the second microporous layer 16 of the carbon fiber paper 10. The solid electrolyte separator 24 facilitates ion transport between the electrodes of the battery while preventing direct electronic contact between them.

[0035] On top of the solid electrolyte separator 24, a cathode layer 26 is applied, forming the positive electrode of the cell structure. The complete structure is then completed with a layer of carbon fiber paper 10, forming a single cell. This configuration represents a coherent electrode assembly, integrating the positive electrode (cathode layer 26), current collector (carbon fiber paper 10), solid electrolyte separator 24, and negative electrode (Si anode layer 22).

[0036] Convert to Figure 2B , which presents an embodiment of a bipolar arrangement of a battery cell. Here, similar to Figure 2A Another complete battery cell structure of one of the stacks is stacked above the existing structure. Each battery cell in the battery stack maintains the same layer sequence as a single battery cell, starting with the carbon fiber paper 10 at the base, followed by the Si anode layer 22, the solid electrolyte separator 24, the cathode layer 26, and finished with the carbon fiber paper 10.

[0037] This bipolar stack design allows for enhanced energy density by allowing series connection of multiple battery cells. The bipolar configuration allows both the anode and cathode to share current collectors, thereby reducing the overall weight and volume of the battery, resulting in a more compact and efficient design. Therefore, this design accommodates multiple electrode assemblies and carbon fiber papers in a staggered manner, where only some adjacent pairs of electrode assemblies are separated by one of the carbon fiber papers. This compact layer arrangement in the bipolar configuration optimizes the performance and efficiency of the battery.

[0038] Reference now Figure 3, showing an expanded battery stack. The configuration starts with a carbon fiber paper (indicated by numeral 30), which is used as a substrate layer. This layer is followed by two single battery cells, indicated by numeral 32. Each of these single battery cells 32 includes several components: a Si anode 34, a solid electrolyte separator 36, a cathode 38, and a substrate layer. The cathode substrate can be an aluminum (Al) foil 40, and the substrate of the anode can be a Cu foil 42. Another layer of carbon fiber paper 30 is placed on these components, followed by subsequent single battery cells 32.

[0039] In this particular arrangement, a Si anode 34 is coated on a Cu foil 42, in accordance with conventional battery manufacturing techniques. However, this structure differs in that a carbon fiber paper 30 is integrated as a strain buffer layer. The role of this layer is to help dissipate mechanical stresses, thereby contributing to the overall durability and life of the battery cell.

[0040] It is worth noting that the carbon fiber paper 30 need not be included for each individual battery 32. Based on experimental determination and the desired properties of the battery, for example, the layer may be included after every 3 to 5 individual battery cells. The exact placement will be determined based on experimental results. By reducing the number of carbon fiber papers 30 in the battery stack, the configuration becomes more compact, thus enhancing the volumetric energy density of the battery.

[0041] The complete structure represents a secondary SSB. It incorporates several electrode assemblies, each of which includes: a positive electrode and a negative electrode, a solid electrolyte separator 36 located between the positive and negative electrodes, and a current collector in direct face contact with the negative electrode. In this design, the negative electrode (Si anode 34) is stuck between the solid electrolyte separator 36 and the current collector (carbon fiber paper 30).

[0042] The secondary SSB configuration also employs carbon fiber papers 30 interlaced with the electrode assemblies. In this arrangement, some but not all adjacent pairs of electrode assemblies are separated by one of the carbon fiber papers 30.

[0043] In further aspects of the depicted embodiments, the current collector may incorporate a carrier film to support structural integrity and better adhesion to the negative electrode. A viable choice for the carrier film may be a polyimide substrate due to its mechanical and thermal stability. The polyimide substrate may be coated with a layer of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (a conductive polymer) to improve the current collection capability of the current collector.

[0044] Now go to Figure 4 , presents a configuration of an elastic material 40 encapsulated between two metal foils 42 and 44. Specifically, in this configuration, an elastomeric material (such as silicone rubber) is used as a central layer, thereby creating an elastic structure suitable for the expansion and contraction behavior of the battery components.

[0045] The roles of the metal foils 42 and 44 are multifaceted. Primarily, they act as conduits to provide electrical connections. Additionally, they function in conjunction with the elastic material 40 to form a compressible structure. This "spring-like" interlayer is designed to contract when the electrode expands during a charge cycle, thereby relieving the strain experienced by the electrode active material. Conversely, when the active material contracts during a discharge cycle, it springs back or expands, thereby ensuring that the particles remain in close contact.

[0046] These adaptive behaviors help maintain the integrity of the battery, thereby enhancing its durability and performance.It should be noted that the properties of the elastic material 40, such as its elastic modulus and thickness, can be precisely designed to meet the specific expansion and contraction requirements of the battery.

[0047] To maintain a compact design of the battery and minimize the overall thickness of the current collector, the thickness of the metal foils 42 and 44 can be kept in the range of 2um to 5um. This careful balance ensures that the battery maintains its energy density while incorporating the strain relief benefits of the elastic layer 40.

[0048] Depending on design requirements and performance requirements, metal foils 42 and 44 can be made of the same material or different materials. In some configurations, both can be Cu, Al, or any other conductive material suitable for application requirements. In other examples, the metal foils may be composed of different materials to optimize certain properties, such as conductivity, mechanical strength, or corrosion resistance.

[0049] The secondary SSB configuration incorporates this current collector design in which the elastomeric material is sandwiched between two metal foils. In this configuration, the negative electrode and the positive electrode are separated by a solid electrolyte separator, and one of the metal foils of the current collector is in direct face contact with the positive electrode, while the other is in contact with the solid electrolyte separator.

[0050] The entire configuration consisting of positive and negative electrodes, solid electrolyte separators, and uniquely designed current collectors forms an electrode assembly. The battery may also include multiple of these electrode assemblies and carbon fiber papers interlaced with the electrode assemblies. This arrangement ensures that some but not all adjacent pairs of electrode assemblies are separated by one of the carbon fiber papers, thereby enhancing the mechanical stability and performance of the battery.

[0051] Now turn to Figure 5 , presents a novel design configuration. Here, metal foam 50 is used as the main elastic component encapsulated by two microporous layers 52 and 54. These microporous layers are composed of nano-sized carbon particles and provide several functionalities to the overall system.

[0052] The microporous layers 52 and 54 serve as important interfaces, contributing to both the mechanical and electrical properties of the assembly. They are used to tune the surface roughness of the metal foam 50, creating a more uniform and beneficial surface. This smooth surface becomes ideal for the subsequent coating of the Si anode layer, helping to enhance its adhesion and uniformity. The microporous layers 52 and 54 also play a key role in enhancing electrical contact, contributing to electrical conductivity within the assembly.

[0053] The metal foam 50 at the heart of the design was chosen for its inherent elasticity. This elasticity allows it to respond to the expansion and contraction of the electrode during the charge-discharge cycle of the battery, thereby enhancing durability and reliability. The elastic properties of the metal foam 50 can be carefully designed to meet desired specifications, thereby ensuring optimal performance in response to the mechanical behavior of the active material.

[0054] The described configuration is integrated into a secondary SSB, where the current collector comprises the metal foam 50 sandwiched between microporous layers 52 and 54. The positive and negative electrodes are separated by a solid electrolyte separator, and one of the microporous layers of the current collector is in direct face contact with the positive electrode, while the other is in contact with the solid electrolyte separator.

[0055] The entirety of the assembly, including the positive and negative electrodes, the solid electrolyte separator, and the uniquely designed current collector, forms an electrode assembly. The battery design may include multiple such electrode assemblies. In addition, the carbon fiber paper may be interlaced with these assemblies so that not all adjacent pairs of the electrode assembly are in direct contact. Instead, some adjacent pairs are separated by the carbon fiber paper, thereby providing additional mechanical stability and enhancing the overall performance of the battery.

[0056] Reference now Figure 6 , a secondary SSB battery cell configuration 60 is introduced. In this embodiment, the strain buffer layer and the current collector form the basic components in a poly (3,4-ethylenedioxythiophene polystyrene sulfonic acid) (PEDOT-PSS) layer 62. The anode layer 64, which can be a Si anode, can be directly coated on the PEDOT-PSS layer.

[0057] The PEDOT-PSS layer 62 itself is coated on a carrier film 66 , such as an insulating polyimide substrate. The polyimide substrate is used to provide structural support for the PEDOT-PSS layer 62 , thereby enhancing the overall mechanical stability of the SSB cell 60 .

[0058] However, depending on the specific cell configuration, the carrier film 66 may remain in the SSB cell stack or be removed. For example, it may be removed in a bipolar cell stack configuration to optimize space and material efficiency.

[0059] To further increase the mechanical strength of the conductive polymer current collector (PEDOT-PSS) 62, the layer can be reinforced with other porous substrates or polymer materials. These can include expanded polytetrafluoroethylene (e-PTFE), glass fibers, cellulose substrates, or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and other options. These reinforcements ensure that the current collector is robust and can withstand the mechanical stresses experienced during battery operation.

[0060] The SSB battery cell 60 as a whole consists of a positive electrode 68, a solid electrolyte separator 70, a negative electrode 64, and a current collector 62. The current collector 62 comprising a PEDOT-PSS layer is in direct surface contact with the negative electrode 64. The negative electrode 64 is in turn positioned between the solid electrolyte separator 70 and the current collector 62.

[0061] The arrangement including the positive electrode 68, the solid electrolyte separator 70, the negative electrode 64 and the current collector 62 forms an electrode assembly. These assemblies can be used to create a secondary SSB including multiple such assemblies. In addition, the carbon fiber paper can be interlaced with these assemblies so that not all adjacent pairs of the electrode assembly are in direct contact. Instead, some adjacent pairs are separated by the carbon fiber paper, thereby providing additional mechanical stability and enhancing the overall performance of the battery.

[0062] Although exemplary embodiments are described above, these embodiments are not intended to describe all possible forms encompassed by the claims. The words used in the specification are words of description rather than limitation, and it should be understood that various changes can be made without departing from the spirit and scope of these disclosed materials.

[0063] As previously described, features of the various embodiments may be combined to form other embodiments of the present disclosure that may not be explicitly described or shown. Although various embodiments may have been described as providing advantages or being preferred over other embodiments or prior art implementations with respect to one or more desired characteristics, it will be appreciated by those of ordinary skill in the art that one or more features or characteristics may be compromised to achieve desired overall system properties, depending on the specific application and implementation. These properties may include, but are not limited to, strength, durability, marketability, appearance, packaging, size, serviceability, weight, manufacturability, ease of assembly, and the like. Therefore, embodiments that are described as being less desirable than other embodiments or prior art implementations with respect to one or more characteristics are within the scope of the present disclosure and may be desirable for a particular application.

Claims

1. A secondary solid-state battery, comprising: Negative electrode; solid electrolyte separator; as well as a current collector comprising a metal foam sandwiched between a pair of microporous carbon layers such that (i) one of the microporous carbon layers is in direct surface contact with the negative electrode and the other of the microporous carbon layers is in direct surface contact with the solid electrolyte separator; and (ii) the surface of the current collector is smoother than the surface of the metal foam.

2. The battery of claim 1, wherein the microporous carbon layer is coated on the metal foam.

3. The battery of claim 1, wherein the microporous carbon layer comprises nano-sized carbon particles.

4. The battery of claim 1, wherein the metal foam is copper metal foam.

5. The battery of claim 1, wherein the thickness of the metal foam is greater than the thickness of each of the microporous carbon layers.

6. The battery of claim 1 further comprising a positive electrode in direct facing contact with the solid electrolyte separator.

7. The battery of claim 6, wherein the positive electrode, the current collector, the solid electrolyte separator, and the negative electrode form an electrode assembly, the battery further comprising a plurality of the electrode assemblies and carbon fiber papers interlaced with the electrode assemblies such that some but not all adjacent pairs of the electrode assemblies are separated by one of the carbon fiber papers.

8. A secondary solid-state battery comprising: Positive and negative electrodes; a solid electrolyte separator between the positive electrode and the negative electrode; as well as A current collector comprising an elastomer sandwiched between a pair of metal foil layers such that (i) one of the metal foil layers is in direct surface contact with the positive electrode and the other of the metal foil layers is in direct surface contact with the solid electrolyte separator, (ii) the current collector compresses in response to expansion of the positive electrode and the negative electrode during charge, and (iii) the current collector expands in response to contraction of the positive electrode and the negative electrode during discharge.

9. The battery of claim 8, wherein the metal foil layers are the same material.

10. The battery of claim 8, wherein the metal foil layers are different materials.

11. The battery of claim 8, wherein the elastomer is silicone rubber.

12. The battery of claim 8, wherein the positive electrode, the current collector, the solid electrolyte separator, and the negative electrode form an electrode assembly, the battery further comprising a plurality of the electrode assemblies and carbon fiber papers interlaced with the electrode assemblies such that some but not all adjacent pairs of the electrode assemblies are separated by one of the carbon fiber papers.

13. A secondary solid-state battery comprising: a plurality of electrode assemblies, each of the electrode assemblies comprising a positive electrode and a negative electrode, a solid electrolyte separator between the positive electrode and the negative electrode, and a current collector in direct surface contact with the negative electrode such that the negative electrode is between the solid electrolyte separator and the current collector, wherein the current collector is a carbon fiber paper current collector comprising a carbon fiber layer sandwiched between a pair of microporous layers; as well as A plurality of carbon fiber papers are interlaced with the electrode assembly.

14. The battery of claim 13, wherein the rough surface of the carbon fiber layer is filled by the microporous layer.

15. The battery of claim 13, wherein some but not all adjacent pairs of the electrode assemblies are separated by one of the carbon fiber papers.